Antecedents of Stock Returns with ROE as a Moderator (Case Study of Non-Cyclical Consumer Sector Companies Listed on the Indonesia Sharia Stock Index 2018-2022) - Reza Amelia; muh nasrullah (Universitas Pekalongan, 2025)
Stock Return is the main condition, goal and reason for purchasing shares. Therefore, investors need to know the antecedents of stock returns so this research was conducted to test, analyze and find out the antecedents of stock returns including operating cash flow, accounting profit, sales growth and company size with ROE as moderating. This research uses a sample of 21 Consumer Non-Cyclicals Sector Companies listed on the Indinesian Sharia Stock Index for 2018-2022 using a sampling technique, namely the purposive sampling method, with a total of 75 data processed. Technical data analysisi uses multiple linear regression tests and Moderated Regression Analysis (MRA) tests using SPSS version 26. The research results show that accounting profits have an effect on stock returns, while operating cash flow, sales growth and company size have no effect on stock returns. Then ROE as a moderator, moderates the influence of sales growth and company size on stock returns, and does not moderate the influence of operating cash flow and accounting profits on stock returns. With these result, it is hoped that this research will contribute to the theorethical development of the field of financial accounting and be able to provide additional information as a reference and consideration for investors in purchasing shares.